2011
DOI: 10.1186/1471-2407-11-226
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic airways inflammation in lung cancer: the role of exhaled LTB-4 and IL-8

Abstract: BackgroundRecent advances in lung cancer biology presuppose its inflammatory origin. In this regard, LTB-4 and IL-8 are recognized to play a crucial role in neutrophil recruitment into airways during lung cancer.Notwithstanding the intriguing hypothesis, the exact role of neutrophilic inflammation in tumour biology remains complex and not completely known.The aim of this study was to give our contribution in this field by investigating LTB-4 and IL-8 in the breath condensate of NSCLC patients and verifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…2B). Our data are consistent with recent studies, which have shown increased levels of IL-8 in lung epithelia as a potent chemoattractant for recruiting inflammatory cells (30,31).…”
Section: Cse Triggers Il-8 Release In Pulmonary Epithelial Cellssupporting
confidence: 93%
“…2B). Our data are consistent with recent studies, which have shown increased levels of IL-8 in lung epithelia as a potent chemoattractant for recruiting inflammatory cells (30,31).…”
Section: Cse Triggers Il-8 Release In Pulmonary Epithelial Cellssupporting
confidence: 93%
“…There are several non-invasive biomarkers measurable in exhaled breath condensate, such as ferritin and superoxide dismutase [130], LTB-4 and IL-8 [131], microsatellite alterations (MAs) at the long arm of chromosome 19 [132], cyclooxygenase (COX-2) and survivin [133], IL-2, TNF-alpha and leptin [134], which, if deemed feasible, have clinical implications in the monitoring of lung cancer and as an religious outcome predictor.…”
Section: Cancermentioning
confidence: 99%
“…16,19 There are vast evidence about the harmful effects of tobacco-derived carcinogen in a variety of ....................................................................................................................... tumor developments, especially in lung cancer. 14,15 However, little is known about the roles of tobacco-derived carcinogen on lung cancer metastasis and invasion.…”
Section: Discussionmentioning
confidence: 99%